Characterization of Borrelia lusitaniae isolates collected in Tunisia and Morocco - Younsi, Hend; Sarih, M'Hammed; Jouda, Fatima; Godfroid, Edmond; Gern, Lise; Bouattour, Ali; Baranton, Guy; Postic, Danièle (My University, 2005)
Borrelia lusitaniae is a species within the complex Borrelia burgdorferi sensu lato and is infrequently isolated in Europe. In contrast, this species is by far the most predominant in North Africa and in Portugal. In this study, we analyzed the genetic diversity, at several loci, of a large population of isolates from free-living Ixodes ricinus ticks collected in Tunisia and Morocco. We found a moderate diversity of the whole genome by using pulsed-field gel electrophoresis as well as in the ospA gene sequences, compared to a high level of strain homogeneity in the small noncoding ribosomal spacer. In contrast, a high diversity of this locus has been previously reported for Portuguese isolates. We hypothesize that B. lusitaniae strains isolated in North Africa constitute a clone of Portuguese origin.
Keywords: BURGDORFERI-SENSU-LATO; IXODES-RICINUS TICKS; FIELD; GEL-ELECTROPHORESIS; 23S INTERGENIC SPACER; LYME-DISEASE; GENETIC; DIVERSITY; SEQUENCE-ANALYSIS; OSPC GENE; 1ST ISOLATION; SP. NOV.